PENGARUH STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Wardani, Dewi Kusuma; Djando, Seventiara Maria Eka Putri (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
The purpose of this study was to determine the effect of capital structure on firm value with good corporate governance as a moderating variable. This study uses a population of manufacturing companies listed on the Indonesia Stock Exchange (IDX). Sampling was based on the purposive sampling method, namely sampling with certain considerations and based on the interests and objectives of the study. This study uses multiple regression analysis techniques. The results of this study found that capital structure has a positive effect on firm value and good corporate governance is able to strengthen the positive effect of capital structure on firm value